Error Analysis on the Students’ Construction of English Irregular Plural Nouns - Mia Amelia Ermanda; Hendar Hendar (Budapest International Research and Critics University, 2022)
In English, the form of singular nouns is commonly different from those of plural ones. Many students are confused about how to construct the irregular plural noun forms. The formation of irregular plural nouns has complex and unique patterns. This current study aims to get information about the types of errors commonly made by EFL learners in constructing irregular plural nouns and to know how the errors occurred. This study used descriptive qualitative applying error analysis theory. The result of the analysis shows that the errors made by the respondents can be classified into three types: 22 data for misformation, 10 data for addition, and 3 data for omission, Misformation was the kind of error most respondents made. The error specifically occurred with the nouns that had quite dissimilar plural forms from the singular ones (e.g., foot – feet, goose – geese).